1977
DOI: 10.1079/bjn19770024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wheat fibre on plasma lipids and faecal steroid excretion in man

Abstract: I. The effect of isoenergetic substitution of bran and wholemeal bread for white flour and white bread was investigated in six healthy volunteers in a metabolic unit. 2.A 21 d high-fibre experimental period was preceded and followed by a 14 d control period, so that each experiment lasted 7 weeks. Blood samples were taken on each of the last 3 d and faeces collected (using carmine markers) for the last 6 d of each diet period.3. Plasma cholesterol, triglycerides and serum calcium concentrations were not altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…In one interesting paper in this group, Munoz et ai. (1979) reported reduction in Eastwood et al (1973) 0 8 men; 16 g bran; 3 weeks Heaton and Pomare (1974) 0 6 normal, 8 cholelithiasis; 38 g bran; 5 weeks Connell et al (1975) 0 23 students; 28-57 g bran; 11 weeks Truswell and Kay (1975); 0 6 normals; 23 g bran + 167 g whole wheat Kay and Truswell (1977a) bread; 3 weeks Jenkins et al (1975a, b) 0 6 men; 30 g bran, 77 g bran products, WW bread; 3 weeks Durrington et aI. (1975) 0 12 men; 30 g bread; 6 weeks Bremner et aI.…”
Section: Wheat Fibrementioning
confidence: 96%
See 1 more Smart Citation
“…In one interesting paper in this group, Munoz et ai. (1979) reported reduction in Eastwood et al (1973) 0 8 men; 16 g bran; 3 weeks Heaton and Pomare (1974) 0 6 normal, 8 cholelithiasis; 38 g bran; 5 weeks Connell et al (1975) 0 23 students; 28-57 g bran; 11 weeks Truswell and Kay (1975); 0 6 normals; 23 g bran + 167 g whole wheat Kay and Truswell (1977a) bread; 3 weeks Jenkins et al (1975a, b) 0 6 men; 30 g bran, 77 g bran products, WW bread; 3 weeks Durrington et aI. (1975) 0 12 men; 30 g bread; 6 weeks Bremner et aI.…”
Section: Wheat Fibrementioning
confidence: 96%
“…Most of these 27 experiments were well designed, with control-test-control (e.g. Kay and Truswell, 1977a) or crossover design (Liebman et aI., 1983) or parallel control groups (Heaton et aI., 1976;Stasse-Wolthuis et aI., 1980) and some were of long duration (Heaton et aI., 1976;Tarpila et aI., 1978;Brodribb and Humphreys, 1976). In some studies all food was provided for the subjects in a metabolic unit (Jenkins et aI., 1975b;Kay and Truswell, 1977a;Raymond et aI., 1977;Stasse-Wolthuis et aI., 1980).…”
Section: Wheat Fibrementioning
confidence: 98%
“…Most of these 27 experiments were well designed, with control -test -control or crossover design or parallel control groups, and some were of long duration. In some studies all food was provided for the subjects in a metabolic unit (Jenkins et al, 1975;Kay & Truswell, 1977;Raymond et al, 1977;Stasse-Wolthuis et al, 1980). In the best of these reports with negative results, frequent measurements were made of plasma cholesterol concentrations.…”
Section: (B) Experiments On Effects Of Cereal Foods or Fractions On Rmentioning
confidence: 99%
“…Contradictory results have been obtained with wheat bran in humans and experimental animals. Jenkins, Hill and Cummings (1975) and Cummings et al (1976) reported increased fecal excretion of bile acids, while Eastwood et al (1973) and Kay and Truswell (1977) dit not observe this increase or even report an increase after bran intake was stopped. In a long-term study (1 year), Tarpila, Miettinen and Mets5ranta (1978) noted a decrease in the fecal elimination of neutral and acid sterols as a result of a decline in cholesterol biosynthesis.…”
Section: Introductionmentioning
confidence: 96%